The Rain Child - Cockrell, Amanda (New York Avon Books, 2001)
Though the white-skinned invaders wreaked havoc on the Cities-in-the-West, the tribes of the Grass have escaped invasion and slaughter. Grandmother Weevil's granddaughter, Flute Dog, a young woman of the Buffalo Horn people, loses her young husband when he is thrown from his horse and trampled on a buffalo hunt. Searching for the horse, Flute Dog finds a pregnant woman wandering in the wilderness. When the woman dies giving birth, Flute Dog decides to raise the baby girl as her own.
Keywords: a